Alteration of factors associated with hepatic gluconeogenesis in response to acute lipopolysaccharide in dairy goat. Issue 6 (1st June 2015) - Wang, L. F.; Yang, G. Q; Yang, S.; Yang, G. Y.; Li, M.; Zhu, H. S.; Wang, Y. Y.; Han, L. Q.; Liu, R. Y.; Jia, S. D.; Song, F.
Abstract: Lipopolysaccharide (LPS) is a common pathogenic agent that causes many diseases and metabolic disorders. Hypoglycemia is often observed when animals are infected with LPS. To explore the influence of LPS on blood glucose and hepatic gluconeogenesis in goats, 12 goats were randomly assigned to 1 of 2 groups: the LPS-treated group (60 μg/kg BW of LPS; jugular vein injections) or the control group (saline vehicle; jugular vein injections). Blood samples were collected from jugular veins at 0, 1, 2, 4, 6, and 8 h, and liver tissue samples were biopsied 8 h after the injections. The dynamic changes in blood glucose levels as well as key hepatic gluconeogenic enzyme mRNA and protein expression, ATP and ADP levels, and glutathione reductase (GR) activity were determined. The results showed that blood glucose levels in the LPS group were dramatically reduced after an initial, short-term increase. In liver tissue, the mRNA of key gluconeogenic enzymes, phosphoenolpyruvate carboxykinase 1 (PEPCK1; P < 0.05), fructose-1, 6-bisphosphatase 1 (FBP1; P < 0.01), pyruvate carboxylase (PCB; P < 0.05), and acyl-CoA synthetase short-chain family member 3 (ACSS3; P < 0.01), in the related pathways and PPAR-γ coactivator 1α (PGC-1α; P < 0.05) were decreased in the LPS group compared with those in the control group, whereas glucose-6-phosphatase (G6Pase-α) was not different ( P > 0.05). The protein expression of PEPCK1 decreased ( P < 0.01), whereas that of G6Pase-α increased ( P < 0.05) significantly. The ratio of ADP to ATP ( P < 0.05) and the activity of GR ( P < 0.01) were markedly increased in the LPS group compared with those in controls. This research showed that LPS markedly affects and reduces blood glucose in dairy goats. The crucial reasons for the marked change in blood glucose are the altered expression of key gluconeogenic enzymes in different pathways and of essential factors associated with gluconeogenesis in the liver.